The Emergence MAC (E-MAC) protocol for wireless sensor networks. (June 2017) - Mickus, Tautvydas; Mitchell, Paul; Clarke, Tim
Abstract: Large scale biological systems often exhibit emergent properties that are attractive in an engineering context. In this paper, the context is a class of wireless sensor networks for emergency environmental monitoring. The attractive properties are simplicity, self-organisation, adaptiveness to scenario change and a lack of scenario-specific parameter tunings. Emergence Medium Access Control (E-MAC) is a scheme inspired by biological social populations that individually react to environmental stimuli. Using a very simple protocol, it exhibits the desired emergent properties. When compared to a well established practical counterpart, the IEEE 802.11 CSMA/CA standard, it exhibits better throughput, end-to-end delay and fairness. This paper describes the motivation and design of E-MAC, and presents the above comparison.